Guideline and Implementation of Osteosarcoma Nursing Care for Children and Adolescents. (11th October 2022) - Gao, Qian; Yao, Yuhong; Xu, Qi
Abstract : Clinical trials on pediatric oncology use therapeutic techniques with the overwhelming majority of children's cancer patients obtaining therapy via clinical investigation procedures. Medical treatment is scheduled according to a specific protocol for enrolled patients. These protocols often do not refer to nursing care. Nursing care, on the other hand, must complement the medical care specified in the medical research protocol. Safe treatment administration, assessment of treatment responses, patients' and families' education, and communication with the whole medical team are just a few of the critical nursing tasks that should be properly managed. Nursing care standards have been developed in this study to strike a good balance between the procedure for clinical research and the nursing care connected with it. These recommendations outline the nursing activities and considerations that must be made while caring for pediatric cancer patients who are engaged in a specific clinical investigation procedure. The objective of this study is to outline the procedure through which nursing care guidelines could be developed and evaluated. The goal of this study was to find out the involvement of nurses in the process of health education for osteosarcoma and family patients.